Tailoring Cu2-xTe quantum-dot-decorated ZnO nanoparticles for potential solar cell applications - Auttasit Tubtimtae (2018)
Cu 2-x Te QDs on ZnO nanoparticles were synthesized using a successive ionic layer absorption and reaction technique (SILAR) at room temperature. The as-synthesized QDs which were distributively deposited on ZnO nanoparticles surface were characterized by field emission scanning electron microscope (FE-SEM), X-ray diffraction and high-resolution transmittance microscope (HR-TEM). It revealed that the average diameter of the QDs was ∼2 nm. The synthesized Cu 2-x Te QDs were solely orthorhombic Cu 1.44 Te phase. The growth mechanism was supposed that it based on ions deposition. The energy gap of as-synthesized Cu 2-x Te QDs was determined ∼1.1 eV and the smallest energy gap of 0.76 eV was obtained, equal to that of bulk material. Raman spectroscopy and FTIR were also used to study the Cu 2-x Te QDs on ZnO nanoparticles. These characteristics suggest a promising implication for a potential broadband sensitizer of QDSCs. © 2014 Elsevier B.V. All rights reserved.